Hematological scoring system as an early diagnostic tool for neonatal sepsis - Fathia Meirina; Bidasari Lubis; Tiangsa Sembiring; Nelly Rosdiana; Olga Siregar (Paediatrica Indonesiana, 2015)
Background Sepsis was the leading cause of death in babies by 30%-50% in developing countries. Early diagnosis of neonatal sepsis is still a difficult problem because of clinical features are not specific. Blood culture is the gold standard, but it takes several days and is expensive. The hematological scoring system (HSS) consists of hematologic parameters (leucocyte count, polymorphonuclear (PMN) cells, degenerative changes, and platelet count) for early diagnosis of neonatal sepsis. Objective To measure HSS as an early diagnostic tool for neonatal sepsis. Methods A cross sectional study was conducted in March to June 2013. Samples were collected by consecutive sampling. Fourty neonates suspected sepsis in neonatology unit H. Adam Malik Hospital, Medan, North Sumatera, underwent routine blood count, blood culture, and peripheral blood smear. Each hematologic parameters were analysed using the HSS of Rodwell et al. The hematologic parameters were total leucocyte count, total PMN cells, total PMN immature, I:T PMN ratio, I:M PMN ratio, degenerative changes, and platelet count. The total value revealed HSS score. Diagnostic study parameters were calculated. Results Ten of fourty neonates had sepsis based on blood culture results. The HSS score >=4 had sensitivity 80%, specificity 90%, with positive predictive value (PPV) 73%, negative predictive value (NPV) 93%, ROC curve showed cut off point 0.902 (95% CI 0.803 to 1.0). Conclusion Score HSS >=4 could be used as an early diagnostic tool for neonatal sepsis.